EARLY HEMODYNAMIC PREDICTORS OF LETHAL OUTCOMES OF ABDOMINAL SEPSIS - I. A. Kozlov; I. N. Tyurin; S. А. Rаutbаrt (Вестник анестезиологии и реаниматологии)
The objective of the study: to find early hemodynamic predictors of a lethal outcome of abdominal sepsis.Methods. 44 patients with abdominal sepsis with no signs of septic shock were enrolled into a retrospective study. The age of patients made 48.7 Ѓ} 2.26 years old; the severity of state according to APACHE II was 12.50 Ѓ} 0.55 scores, and as per SOFA ‒ 8 [6; 10]) scores. Hemodynamics was assessed through transpulmonary thermodilution.Results. During the first 24 hours, the following rates were the most sensitive and specific in respect of a lethal outcome: cardiac function index (odds ratio – 0.582; 95%CI 0.388-0.872; p = 0.008), and cardiac power index (odds ratio – 0.027; 95%CI 0.001-0.6; p = 0.022). The same results were observed in 4-5 days of treatment. At different stages of the study, the following rates demonstrated stable predictive significance: cardiac index (CI), systolic output index, global ejection fraction; and the area under ROC-curves (AUROC) for these rates was compatible with AUROC as per SOFA.Conclusion: The investigation of the after-load dependent relative cardiac efficiency proved that the normal values of CI could be predictive of an unfavorable sepsis outcome if after-load dependent relative cardiac efficiency was < 80%. It is sensible to define individual target values of cardiac hemodynamics, which significance is clinically proved in case of sepsis.